اخلاقی اور فقہی چیلنجر(AI):اسلام اور مصنوعی ذہانت: ISLAM AND ARTIFICIAL INTELLIGENCE (AI): ETHICAL AND JURISPRUDENTIAL CHALLENGES (Al-Aasar, 2025)
Artificial Intelligence (AI) represents a technological revolution that has profoundly transformed various aspects of human life. Its applications extend beyond industrial and commercial sectors to education, healthcare, social interactions, and human decision-making processes. The rapid advancement of AI has raised numerous ethical, social, and legal questions that require not only technical solutions but also philosophical and religious guidance. Islamic teachings encourage the pursuit of knowledge and innovation; however, these must always operate within the boundaries of human welfare, social justice, and moral principles. The Quran and Sunnah emphasize the protection of human dignity, ethical conduct, and social well-being, providing a guiding framework for the responsible implementation of modern technology.This study examines AI from the perspective of ethical and jurisprudential challenges and analyzes how Islamic teachings can guide the responsible, human-centered, and morally grounded use of technology. Issues such as autonomous decision-making by AI systems, their impact on human life, and adherence to ethical limits must be understood in the light of Islamic principles. Islam emphasizes justice, equity, transparency, and the protection of human rights, offering a comprehensive ethical and jurisprudential framework that can govern the practical application of AI systems.The purpose of this research is to establish a balance between modern technology and Shariah principles, ensuring that AI systems operate in alignment with human welfare and social justice. Islamic jurisprudential and ethical guidance provides a framework that is not only technically effective but also safeguards human rights and promotes societal well-being. This introduction underscores the necessity of applying Islamic ethical and jurisprudential principles to AI, ensuring that this technological revolution advances in harmony with human development, moral responsibility, and social welfare.